Efficacy and Safety of Topical Fipronil 1% and Deltamethrin 0.1% in Water Buffaloes (Bubalus bubalis) Naturally Infested by Haematopinus tuberculatus - Buitrago, Jhon Didier Ruiz; Zuluaga, Edison A. Cardona; Gutiérrez, Jesús Alfredo Berdugo; Arboleda, Wilder Cardona (Journal of Buffalo Science, 2018)
Haematopinus tuberculatus is the main arthropod affecting buffaloes around the world. It causes intense itching and restlessness, altering feeding habits, thus reducing animal productivity. This parasitosis is seldom studied, as it does not lead to significant animal mortality or financial losses. In this project, we evaluated the efficacy and safety of two commercially available products for control of pediculosis in naturally infested buffaloes. A total of 24 milk producing, clinically healthy female buffaloes that were naturally infested by lice were included in this study. Animals were equally distributed into two groups: group 1 was treated with a single dose of pour on Fipronil (1%, Carval de Colombia, 1 ml of product per 10 kg of live weight). Group 2 was treated with a single dose of deltamethrin (5%, Bioara, SA), at a final concentration of 0,1% applied with an aspersion pump as a single bath of 4 liters of diluted solution per animal. Lice were counted weekly from day 1 to day 58 post-treatment. Up to day 23 post-treatment, no significant differences in efficacy were observed between products.Fipronil 1% consistently exhibited an efficacy above 70% from day 8 and until 30 day of the study. These results suggest that both products are efficient and safe to control lice infestations in buffaloes. However, fipronil 1% exhibited a greater residual effect, which reduces the number of baths required to treat infested animals, and reduces the probability of selecting for drug-resistant lice populations